2006
DOI: 10.1111/j.1365-313x.2006.02861.x
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid‐mediated and RNA‐silencing defense mechanisms cooperate in the restriction of systemic spread of plum pox virus in tobacco

Abstract: SummaryPlum pox virus (PPV) is able to replicate in inoculated leaves of Nicotiana tabacum, but is defective in systemic movement in this host. However, PPV produces a systemic infection in transgenic tobacco expressing the silencing suppressor P1/HC-Pro from tobacco etch virus (TEV). In this work we show that PPV is able to move to upper non-inoculated leaves of tobacco plants expressing bacterial salicylate hydroxylase (NahG) that degrades salicylic acid (SA). Replication and accumulation of PPV is higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
117
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 54 publications
(146 reference statements)
3
117
0
1
Order By: Relevance
“…Exogenous SA can also inhibit cell to cell movement in epidermal cells (Murphy and Carr, 2002). Moreover, it was found that Plum pox virus (PPV; defective in systemic movement) was able to move to distal tissues in transgenic tobacco plants expressing bacterial salicylate hydroxylase (NahG) which degrades SA (Alamillo et al, 2006). Based on this evidence, it was proposed that SA plays a positive role in antiviral resistance by interfering with different steps of the viral cycle (Chivasa et al, 1997;Murphy and Carr, 2002;Alamillo et al, 2006).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…Exogenous SA can also inhibit cell to cell movement in epidermal cells (Murphy and Carr, 2002). Moreover, it was found that Plum pox virus (PPV; defective in systemic movement) was able to move to distal tissues in transgenic tobacco plants expressing bacterial salicylate hydroxylase (NahG) which degrades SA (Alamillo et al, 2006). Based on this evidence, it was proposed that SA plays a positive role in antiviral resistance by interfering with different steps of the viral cycle (Chivasa et al, 1997;Murphy and Carr, 2002;Alamillo et al, 2006).…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
“…Orthologous genes of NtRDR1 have also been characterized in other species, such as Nicotiana glutinosa (NgRDR1), Nicotiana benthamiana (NbRDR1m), A. thaliana (AtRDR1), Medicago truncatula (MtRDR1) and rice (OsRDR1), all of them being induced by both viral infection and SA treatment (Yu et al, 2003;Yang et al, 2004;Quilis et al, 2008;Liu et al, 2009). Several findings indicate that RDR1 could be involved in the SA-induced resistance against viruses (Alamillo et al, 2006;Lee et al, 2016). The impact of SA on the modulation of RDR1 action was demonstrated in tobacco NahG transgenic plants infected with PPV.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
See 3 more Smart Citations